First record from Europe of the Asian bamboo-feeding leafhopper Trifida bilobata Ohara, 2014 (Hemiptera: Cicadellidae: Typhlocybinae) - Poggi, Francesco; Sanna, Francesco; Casiraghi, Alice; Šćiban, Marko; Kunz, Gernot (Zootaxa, 2024)
The Asian bamboo-feeding leafhopper Trifida bilobata Ohara, 2014 from Japan, is recorded for the first time in several European countries (Spain, Switzerland, Italy, Austria and Serbia). Morphology and ecology of the collected specimens in Europe are presented.